Financial Market Volatility and the Implications for Market Regulation : A Survey - Scott, Louis (IMF Working Papers; Working Paper, 1990)
Volatility in financial markets has forced economists to reexamine the validity of the efficient markets hypothesis, and new empirical approaches have been applied to the study of this important issue in recent years. Many of the recent studies have found evidence of excessive volatility. In the aftermath of the stock market crash of 1987 and the perceived increase in market volatility, some economists have advocated additional market regulations. Are these proposed regulations necessary and would they serve to reduce market volatility? This paper presents a review of recent studies on financial market volatility and examines the proposed regulations.